The great derangement: climate change and the unthinkable - Ghosh, Amitav (University of Chicago Press, 2016)
"Are we deranged? The acclaimed Indian novelist Amitav Ghosh argues that future generations may well think so. How else to explain our imaginative failure in the face of global warming? In his first major book of nonfiction since In an Antique Land, Ghosh examines our inability at the level of literature, history, and politics to grasp the scale and violence of climate change. The extreme nature of today's climate events, Ghosh asserts, make them peculiarly resistant to contemporary modes of thinking and imagining. This is particularly true of serious literary fiction: hundred-year storms and freakish tornadoes simply feel too improbable for the novel; they are automatically consigned to other genres. In the writing of history, too, the climate crisis has sometimes led to gross simplifications; Ghosh shows that the history of the carbon economy is a tangled global story with many contradictory and counter-intuitive elements. Ghosh ends by suggesting that politics, much like literature, has become a matter of personal moral reckoning rather than an arena of collective action. But to limit fiction and politics to individual moral adventure comes at a great cost. The climate crisis asks us to imagine other forms of human existence a task to which fiction, Ghosh argues, is the best suited of all cultural forms. His book serves as a great writer's summons to confront the most urgent task of our time."